Resilience in healthcare supply chains: a review of the UK’s response to the COVID19 pandemic - Sawyerr, Emmanuel; Harrison, Christian (Emerald, 2022)
Purpose The purpose of this explorative research is to analyse the resilience of the United Kingdom's (UK) healthcare supply chains from a customer’s perspective in the light of the coronavirus pandemic. Design/methodology/approach Using the capabilities of preparedness, robustness, recovery and adaptability as the foundational percept for supply chain resilience, 22 healthcare professionals in 17 of the UK's National Health Scheme (NHS) Trusts were interviewed to explore their personal and organisational approaches adopted relative to the provision of eye protection, gloves, gowns, aprons, masks and respirators. The Dynamic Capabilities View is mapped to the resilience capabilities and used to analyse the data from a transformational supply chain research perspective. Findings The supply chains were largely unprepared, which was not particularly surprising even though the availability of gloves was significantly better compared to the other personal protective equipment (PPE). Techniques adopted to ensure robustness and recovery revealed the use of unsanctioned methods such as extended use of PPE beyond recommended use, redefinition of guidelines, protocols and procedures by infection control and the use of expired PPE – all of which compromised customer well-being. Research limitations/implications As the paper views resilience through the lens of customers, it does not provide the perspectives of the supply chain practitioners as to the reasons for the findings and the challenges within these supply chains. Practical implications The compromise of the well-being of healthcare workers due to the vulnerabilities of healthcare supply chains is highlighted to managers and prescriptions for post-disruption adaptability are made. Originality/value This paper introduces transformative research to supply chain resilience research by uniquely looking at resilience from the customers' well-being perspective.
Keywords: Supply chain resilience; Dynamic capabilities; Personal protection equipment; Healthcare supply chains; COVID19 pandemic; Transformative supply chain research